2018
DOI: 10.1080/01443615.2017.1371119
|View full text |Cite
|
Sign up to set email alerts
|

Non-indicated use of prophylactic antibiotics in gynaecological surgery at an academic tertiary medical centre

Abstract: Surgical site infections (SSI) are the most common surgical complication. Perioperative antibiotics can reduce SSI when used properly. Despite guidelines from The American College of Obstetrics and Gynecology, non-indicated antibiotic use is widespread which exposes women to unnecessary risks. This study represents a quality improvement analysis assessing surgeon compliance with established guidelines regarding antibiotic use in gynaecological surgery. This is a single centre, retrospective study examining gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Some of the more common reasons for using antibiotics unnecessarily in the perioperative setting include entrance into abdominal cavity, higher estimated blood loss, and longer procedures. 7 Although clinical guidelines for antibiotic prophylaxis across a wide array of surgical procedures have been proposed by a collaborative, multidisciplinary group of physicians and pharmacists, 8 widely cited, and reiterated, 9 clinicians often deviate from recommendations, especially when recommendations are based on weak data. The goal of this review is to highlight certain common but controversial topics in perioperative prophylaxis.…”
mentioning
confidence: 99%
“…Some of the more common reasons for using antibiotics unnecessarily in the perioperative setting include entrance into abdominal cavity, higher estimated blood loss, and longer procedures. 7 Although clinical guidelines for antibiotic prophylaxis across a wide array of surgical procedures have been proposed by a collaborative, multidisciplinary group of physicians and pharmacists, 8 widely cited, and reiterated, 9 clinicians often deviate from recommendations, especially when recommendations are based on weak data. The goal of this review is to highlight certain common but controversial topics in perioperative prophylaxis.…”
mentioning
confidence: 99%
“…Joyce et al (2015) who studied 326 surgeries performed from 2012 to 2013 at tertiary care hospital found that PAP was used in 53.7% of procedures with no indication. More recently, Kremer et al (2018) analyzed 2,961 gynecological cases at a tertiary hospital and found that the overall proportion of preoperative antibiotic use for procedures in which antibiotics were not indicated was 19%. The study from Abubakar et al (2018) that evaluated compliance with surgical antibiotic prophylaxis in obstetrics and gynecological surgeries performed at 3 tertiary hospitals in Nigeria found the proportion of unnecessary antianaerobic combination to be as much as 89.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportion of non-indicated preoperative antibiotics was significantly high, reaching almost 90%. In fact, there was no record of occurrences that could justify such use, for instance, prolonged surgery, unplanned entrance into the abdomen or excessive blood loss (Kremer et al, 2018). The overuse of antibiotics is well known to increase patient morbidity and healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations